2007
DOI: 10.1108/00400910710762922
|View full text |Cite
|
Sign up to set email alerts
|

The implications of contemporary cultural diversity for the hospitality curriculum

Abstract: PurposeThis viewpoint paper aims to assess a curriculum response within a specific vocational sector, hospitality, driven by the recent surge in intra EU labour migration and the ensuing increase in workplace cultural diversity.Design/methodology/approachThe paper identifies an appropriate curriculum response by assessing the industry implications and proffering a conceptual model of curriculum response.FindingsThe experience across business sectors, such as hospitality, emphasises the need for training that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
1
25
0
2
Order By: Relevance
“…Although no studies were found that addressed gender issues in hospitality curriculum, Hearns, Devine, and Baum (2007) explored the curriculum implications of cultural diversity in the workplace. They examined a conceptual model that included course content, learning outcomes, assessment methods, and the training needs of educators, and they concluded that awareness of workplace diversity can and should be taught.…”
Section: Hospitality Curriculummentioning
confidence: 99%
“…Although no studies were found that addressed gender issues in hospitality curriculum, Hearns, Devine, and Baum (2007) explored the curriculum implications of cultural diversity in the workplace. They examined a conceptual model that included course content, learning outcomes, assessment methods, and the training needs of educators, and they concluded that awareness of workplace diversity can and should be taught.…”
Section: Hospitality Curriculummentioning
confidence: 99%
“…For example, one of the research teams believed it appropriate to pay survey participants, whilst at one meeting representatives of one institution were unable to communicate in either English or German and hence could not speak to the other researchers. The impact that diverse cultural and academic practices had on the research process (Weetman, 2006;Hearns et al, 2007) is impossible to quantify, however, there is little doubt that participation in the study promoted a degree of mutual understanding and added to the richness of the study findings. Moreover, the use of qualitative methods within a European context 273…”
Section: The Study Approachmentioning
confidence: 99%
“…Multiculturalism may need to be understood not only as a training for competencies geared towards managing diversity, but rather a process of educating students and staff for integration in an intercultural working environment. It is believed colleges and universities, offering hospitality and tourism programmes, can readily support learning in these areas by providing greater focus within their curricula to legal and other aspects of multiculturalism and multi-ethnicity [13]. It is certainly important to teach students from a variety of perspectives about sustainability to lessen hospitality and tourism's negative impacts and maximize its positive impacts in general, but more specifically teaching sustainability is important because a destination's natural and cultural resources are tremendously strategic resources [2].…”
Section: Breakthrough Innovation and Strengthening Innovation Systemsmentioning
confidence: 99%